Plasmodium knowlesi gametocyte carriage and load among malaria patients at Kapit Hospital in Sarawak, Malaysian Borneo - Darvindran, Theivindran; TING HUEY, HU; Dayang Shuaisah, Awang Mohamad; Nawal, Rosli; King Ching, Hii; Balbir, Singh; Angela, Siner (Springer Nature, 2025)
The number of human infections with Plasmodium knowlesi, a malaria parasite typically found in long-tailed and pig-tailed macaques, have increased and P. knowlesi has become the sole cause of indigenous cases of malaria in Malaysia since 2018. The reasons for the increase are multifactorial and could include human-to-human transmission through mosquito bites. Such transmission would require viable gametocytes circulating in the blood of infected individuals as this is the only parasite blood stage transmissible to mosquitoes. The objectives of this study were to determine the proportion of P. knowlesi malaria patients with viable gametocytes and to determine the association between gametocyte load and duration of illness prior to hospital admission, and with total parasitaemia. The mRNA transcripts of pks25, a gene expressed in mature female P. knowlesi gametocytes, were measured by a real-time PCR assay in blood samples from 295 patients at Kapit Hospital, Sarawak, Malaysian Borneo with PCR-confirmed single infections of P. knowlesi. Viable gametocytes were present in 67.5% (199/295) of patients. A positive correlation was seen between gametocyte load and total parasitaemia (ρ = 0.32, p = 0.01), whereas there was no statistically significant association between gametocyte carriage and duration of illness prior to hospitalisation (ρ = 0.28, p = 0.7). Forty (20%) of 199 gametocyte-positive samples had fewer than 500 pks25 transcript copies/μL, but 25 (12.5%) of 199 gametocyte-positive patients had elevated levels of gametocytes; 13 (10.8%) had between 10,001 and 100,000 and 12 (6%) had > 100,000 pks25 transcript copies/μL. Our findings demonstrate the presence of viable gametocytes in a substantial proportion of patients, including some with relatively high densities. This observation, taken together with other findings, underscores the potential of humans to serve as infectious hosts of P. knowlesi, but they do not constitute direct evidence of human-to-human transmission. Significant gaps still remain in our understanding of P. knowlesi gametocyte biology and infectivity. Addressing these gaps is essential to ascertain whether human-to-human transmission of P. knowlesi, which was experimentally demonstrated in the 1960s, occurs in natural settings. Continued surveillance of human P. knowlesi infections together with studies on gametocyte biology, vector bionomics, and monitoring of macaque host populations in relation to environmental alterations are vital to understand changes in the dynamics of P. knowlesi malaria transmission, and to inform strategies for its control and prevention.